Design and optimization of a modified series hybrid electric vehicle powertrain. (May 2019) - Borthakur, Swagata; Subramanian, Shankar C
Hybrid electric vehicles are emerging technologies that are considered as eco-friendly alternative solutions to internal combustion engine–driven vehicles. This paper proposes a modified hybrid electric vehicle powertrain system that addresses the shortcomings of a series hybrid electric vehicle powertrain. The proposed configuration replaces the conventional generator of a series hybrid electric vehicle with an integrated starter generator that supports the traction motor of the vehicle during acceleration and peak torque requirements and maintains the state of charge of the batteries to provide an extended electric range of the vehicle. The work done in this paper can be categorized into two stages. The first stage is the methodical development of the powertrain in terms of initial parameter matching and sizing of the vehicle components by considering the fundamentals of longitudinal vehicle dynamics. The second stage describes the optimization of the proposed configuration to meet the design objective of maximizing fuel economy subjected to a set of vehicle performance constraints. The performance of the proposed powertrain was evaluated and compared with a series hybrid electric vehicle powertrain for an on-road Indian driving cycle using AVL CRUISE, which is a commercially available software for the study and analysis of road vehicle powertrains. Result analysis during initial parameterization showed a reduction in gross vehicle weight of the proposed configuration by 244 kg (1.5%) and an improvement in the average operating efficiency of the traction motor by around 11%, when compared to a series hybrid electric vehicle. Furthermore, the optimization results for the proposed configuration established an improvement in the fuel economy by 21% while meeting vehicle performance requirements.